Politics at the City of David - Shanks, Hershel (The Biblical archaeology review, 1981)
The dispute which sporadically disrupted the archaeological excavations in the City of David last summer had nothing to do with archaeology and everything to do with politics. The incident demonstrated that Judaism, like other religions, has its lunatic fringe.